International peacebuilding and local contestations of notions of human rights in Acholi in Northern Uganda - Omach, Paul (Third World Quarterly, 2020)
This paper examines the contestation over human rights norms between Acholi traditional authorities and everyday realities on the one hand, and international peacebuilding actors on the other. Within this contestation, the focus is on women’s and children’s rights. When implementing human rights programmes, some international peacebuilding actors presented culture and rights as conflictual and attributed human rights violations to culture. This created tension between Acholi traditional authorities and everyday realities on the one hand, and international peacebuilding actors on the other. The paper argues that Acholi traditional authorities responded to the ‘assault’ on Acholi cultural values by presenting alternative narratives of human rights violations, to show that culture and rights overlap and are not conflictual.
Keywords: human rights; peacebuilding; conflict; colonialism cultural; norms; Northern Uganda